Pandemic, policy, and pedagogy: analyzing the tripartite role of COVID 19 pandemic, National Education Policy 2020, and pedagogical innovations vis-a-vis educational implications - Aditi; Deepa Idnani (Center for Humanities and Innovation Studies, 2021)
The paper draws interlinkages between three factors, i.e., COVID-19 pandemic, the release of National Education Policy (NEP), 2020 by the Government of India, and the need for pedagogical changes and innovations concerning their educational implications the Indian context. The paper argues that COVID-19 pandemic has been a major setback for the ailing academic infrastructure in India. The immediate outcome might cause the severity of the pandemic and the increasing cases of infections across the nation, and the closure of schools and other educational institutions. However, to overcome further educational losses and compromises, the schools and colleges alternatively moved to online modes haphazardly. Ever since this transition happened, everyone has been trying to adapt to this new 'normal’. Despite the relentless working of stakeholders at various levels owing to these unprecedented times, the situation does not look inspiring. Though NEP 2020 was envisioned as a sigh of relief and a major game-changer in metamorphosing the educational system in India, particularly the learning gaps induced due to the ongoing pandemic. This paper attempts to investigate the dynamics of the major debates emerging as a result of the anxieties and upheavals posed by the COVID-19 pandemic: the response of various stakeholders such as administrators, policymakers, teachers, educators, learners etc. and the pedagogical implications for the teachers and educators due to these uncertain circumstances.